Fire behaviour of carbon fibre epoxy composite for aircraft: Novel test bench and experimental study. (May 2015) - Tranchard, Pauline; Samyn, Fabienne; Duquesne, Sophie; Thomas, Matthieu; Estèbe, Bruno; Montès, Jean-Luc; Bourbigot, Serge
A versatile fire test has been developed with a complete set of instrumentation to investigate the fire behaviour of carbon fibre epoxy composite designed for aircraft. During a single test, both condensed and gas phases can be simultaneously studied measuring the temperature profile and the mass loss and studying the nature and quantity of volatile gaseous species. This novel test bench is compliant with two aeronautical certification fire tests: ISO2685:1998(E) and FAR25.856(b):2003. Titanium coupons have been first submitted to fire to validate the testing method. Composite coupons have been evaluated to examine completely their fire behaviour. To go further in the investigation, post-fire analyses have been performed using X-ray microtomographic images of coupons exposed to fire. Thus, the phenomena identified during the test are the apparition of cracks in the virgin material, the thermal degradation, the migration of evolved gases through the material up to both side and the thermal delamination.